Study of terminology of crisis management - Veres Somosi, Mariann; Pererva, P. G. (Національний університет "Львівська політехніка", 2017)
Thus, from our point of view, we can interpret the term "crisis management" as organized on a permanent basis the company's management considers a set of economic relations concerning the revealing signs of a crisis condition of the enterprise and its prevention.
Keywords: crisis; terminology; management; development; economics; organization